Clinical Profile and Outcome of Acute Encephalitis Syndrome in Dhulikhel Hospital of Nepal - Dongol, Srijana; Shrestha, Shreema; Shrestha, Narayan; Adhikari, J (Journal of Nepal Paediatric Society, 2013)
Introduction: Acute encephalitis syndrome (AES) is a constellation of clinical signs and or symptoms i.e. acute fever with acute change in mental status. AES may be present as encephalitis, meningoencephalitis or meningitis. It can be associated with severe complication, including impaired consciousness, seizure, limb paresis or death. Materials and Methods: Study consisted of retrospective analysis of hospital records of children up to 16 years of age admitted with diagnosis of AES in the department of Paediatrics Dhulikhel Hospital, Kathmandu University Teaching Hospital, Dhulikhel Kavre from January 2010 to December 2011. Results: During the two years (January 2010 to December 2011), 47 patients of AES were admitted. Among the admitted cases there were 34 male and 13 female patients. Meningitis cases were 29, encephalitis cases were 14 and 4 meningoencephalitis cases. Among the meningitis cases, viral meningitis accounted for 12, bacterial meningitis accounted for 15 and 1 tubercular meningitis.One was eosinopilic meningitis in which the causative organism was found to be fasciolosis by ELISA. Viral encephalitis was found to be the most common cause of encephalitis. Sensorineural hearing loss was seen in 3 cases, subdural effusion in 1 and hydrocephalus in 1. One patient had intracranial hemorrhage with hemiparesis as a complication of eosinophilic meningitis. Conclusion: Acute encephalitis syndrome is one of the most common causes of PICU admission in Dhulikhel hospital. Bacterial meningitis was common among the acute encephalitis syndrome followed by viral meningitis. One case of eosinophilic meningitis with intracranical hemorrhage and hemiparesis was found. Sensorineural hearing loss was found to be commonest complication. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6683 J. Nepal Paediatr. SocVol.32(3) 2012 201-205